Nature Reviews Disease Primers - Razzak, Mina.; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Research.)
Nature Reviews Disease Primers publishes introductory review articles, called Primers, that each cover one disease or disorder. Each Primer will cover the epidemiology, disease mechanisms, diagnosis and treatment (current and future) of the disease. Like all the other Nature Reviews journals, this commissioned journal contains highquality artwork with text provided by internationally recognised researchers. The journal aims to cover all the major diseases within five years of launch and will become an invaluable resource for researchers and educators alike.
Keywords: Cancer research; Medical microbiology; Medicine; Internal medicine; Epidemiology; Quality of life; Medicine/Public Health, general; Epidemiology; Internal Medicine; Quality of Life Research; Medical Microbiology; Cancer Research